2014
DOI: 10.25011/cim.v37i6.22243
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of ITCH is associated with down-regulation of LATS1 during tumorigenesis and progression of cervical squamous cell carcinoma

Abstract: Purpose: The molecular basis for the normal cervical squamous epithelium advance to cervical intraepithelial neoplasia (CIN I, CIN II, CIN III) and ultimately to invasive carcinoma has not yet been defined. We explored the abnormal expression of ITCH (AIP4) and its degrading substrate Large Tumor Suppressor 1 (LATS1) in CINs and cervical cancers, which might disrupt the normal differentiation of the cervical epithelia and contribute to the tumorigenesis of the cervix. Methods: A series of 110 samples, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that LATS1 expression is downregulated in malignant tumors, including CSCC [ 10 ], breast cancer [ 11 ] and HCC [ 12 ]. To examine the expression of LATS1 in GC tissues, we detected the expression level of LATS1 in 89 cases of GC patients with paired adjacent non-tumor tissue (ANTT) by IHC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that LATS1 expression is downregulated in malignant tumors, including CSCC [ 10 ], breast cancer [ 11 ] and HCC [ 12 ]. To examine the expression of LATS1 in GC tissues, we detected the expression level of LATS1 in 89 cases of GC patients with paired adjacent non-tumor tissue (ANTT) by IHC.…”
Section: Resultsmentioning
confidence: 99%
“…The representative members of LATS family, such as LATS1 and LATS2, a kind of Ser/Thr kinase originally isolated from Drosophila [ 6 , 7 ], are implicated in many crucial life processes including cell proliferation, cell apoptosis and cell migration [ 8 ] and surveillant behaviors in transcriptional regulation and maintenance of genetic stability [ 9 ]. Aberrant expression or gene mutation of LATS1 contributes to malignant transformation and histological progression in cervical squamous cell carcinoma (CSCC) [ 10 ], breast cancer [ 11 ], hepatocellular carcinoma (HCC) [ 12 ] and astrocytoma [ 13 ]. Overexpression of LATS1 significantly suppresses human renal carcinoma cell growth and tumorigenicity in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…LATS1 and LATS2 have been implicated in a number of human malignant tumors. Abnormal expression or gene mutation of LATS1 contributes to malignant transformation and histologic progression in cervical squamous cell carcinoma [ 13 ]. Down-regulation of LATS1 and LATS2 is correlated in breast cancer with alterations of p53 function and cell migration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression or mutation of LATS has been found to be involved in malignant transformation and pathological progression of cervical squamous cell carcinoma, breast cancer, and hepatic malignancies [ 13 14 15 ]. However, the expression of LATS in gastric cancer and its implications have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical samples of normal and neoplastic cervix, increased expression of upstream regulator ITCH and decreased expression of LATS1 was associated with transformation of cervical epithelial cells and progression of cervical squamous cell carcinoma (Zhou et al, 2014). In cervical cancer patients high ITCH or low LATS1 expression was associated with increased clinical stage and tumor size.…”
Section: Cervical Cancermentioning
confidence: 92%